Treatment of post-traumatic parotid gland fistula in children - Carmine Noviello; Mercedes Romano; Giulia Delehaye; Alfonso Papparella (Elsevier, 2022)
Post-traumatic fistula of the parotid gland is rare especially in children and the treatment is not established: surgery, drugs or conservative treatment. The authors present the case of a 3-year-old child with cutaneous-parotid fistula following penetrating trauma of the face. A conservative treatment with compression dressings was used and one month later a complete closure of the fistula was obtained. In this case a conservative approach should be considered because the part of the fistulized gland goes into atrophy and allows the closure of the fistula.